A checklist of trichodinid species (Ciliophora: Trichodinidae) on tilapia fishes (Cichlidae), with new records from Mexico and the first data from Argentina - Islas-Ortega, Alma G.; Marcotegui, Paula S.; Basson, Linda; Aguilar-Aguilar, Rogelio (Zootaxa, 2020)
Tilapia is the common name for a wide spectrum of cichlid fishes usually selected for aquaculture activities. However, some aspects of the natural history of these fishes, such as the diversity of certain ectoparasitic protistan groups remain understudied. In order to understand the diversity of ciliates of the family Trichodinidae parasitizing tilapia around the world, a database with all available accounts was assembled. This information, along with records derived from our own recent research, allowed us to generate a checklist containing all the records for tilapia-Trichodinidae associations. The checklist is presented as a host-parasite list containing 44 nominal taxa from 29 countries on four continents, and it also presents the first data from Argentina, where tilapia culture is still an incipient, but growing activity. The observed high species richness of trichodinids is probably derived from a set of specific taxa for tilapia, along with an important component of species acquired from the new environments where tilapia have been introduced. Data presented here could be used along with existing information of metazoan parasites to build a general view about diseases that affect tilapia.